Coal Dust and Methane as a Hazard in Coal Preparation Plants - Aleksander Lutyński; Marcin Lutyński (Applied Sciences)
This article presents the results of analysis of the hazards posed by coal mine dust and methane in the coal preparation plants of hard coal mines in Poland. It was shown how the number of workplaces in plants at risk of coal dust explosion and the highest permissible dust concentration changed in the period from 2003 to 2022 when compared with coal production. The methodology of assessing mine dust hazards was based on hazard ratios related to one million tons of hard coal enriched in preparation plants. As a result of the analysis, it was found that the explosion hazard index with zone 20 showed an increasing trend in the analyzed period, while the explosion hazard indices with zones 21 and 22 analyzed together and the maximum permissible dust concentration showed decreasing trends following a decrease in hard coal production. In the case of methane, no zone 0 explosion hazards were found, and there were only a few instances of zone 1 explosion hazards. However, it was determined that the explosion hazard index for zone 2 showed an increasing trend during the analyzed period, which is directly proportional to the coal produced and is a result of increasing depth of mining.